Transient elastic‐plastic‐creep crack‐tip stress fields under load‐controlled loading. Issue 4 (10th November 2017) - Lee, H.‐S.; Kim, D.‐J.; Kim, Y.‐J.; Ainsworth, R.A.; Budden, P.J.
Abstract: This paper presents transient and steady‐state elastic‐plastic‐creep crack‐tip stress fields under load‐controlled loading conditions for a wide range of combinations of power‐law plastic and creep materials. The crack‐tip stress fields are characterized in terms of 2 parameters to accommodate the crack‐tip constraint effect; the C ( t ) ‐ (or C*‐ ) integral and the βQ parameter (the Q ‐parameter normalized with respect to the proximity parameter to plastic collapse). For practical application, the crack‐tip stress fields are re‐formulated explicitly in terms of time and crack‐tip stress fields for elastic‐plastic and steady‐state creep conditions. Comparison with detailed FE results for plane strain tension and bend specimens shows that this formulation of the crack‐tip stress fields agrees well with finite element results.